2017
DOI: 10.1038/s41598-017-06465-9
|View full text |Cite
|
Sign up to set email alerts
|

Host plants and obligate endosymbionts are not the sources for biosynthesis of the aphid alarm pheromone

Abstract: (E)-β-farnesene (EβF) is the major component of the alarm pheromone of many aphid species, but where EβF is synthesized in aphids is only partly understood. There are at least three most possible sources for the alarm pheromone: host plants, aphid obligate endosymbiont and aphids themselves. Here we eliminated the possibility of host plants and the obligate endosymbiont Buchnera aphidicola as the sources for EβF released by aphids. We excluded the possible effects of host plants on EβF biosynthesis by rearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The EβF content in the aphid was quantitatively measured after RNAi by using the method modified from Fischer and Lognay () and Francis et al (). Briefly, the emitters with secretion were put into 2 ml microcentrifuge tubes on the ice which contained 200 μl of distilled hexane and 0.2 μl decane (purity > 99.9%) as an internal standard for quantification by gas chromatography–mass spectrometry (Sun and Li, ). The non‐emitters were placed in 1.5 ml microcentrifuge tubes, and both emitters and non‐emitters were weighed on an electronic analytical balance (A200S, 0.0001 g, Sartorius) for calculating the concentration of EβF per milligram of aphid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EβF content in the aphid was quantitatively measured after RNAi by using the method modified from Fischer and Lognay () and Francis et al (). Briefly, the emitters with secretion were put into 2 ml microcentrifuge tubes on the ice which contained 200 μl of distilled hexane and 0.2 μl decane (purity > 99.9%) as an internal standard for quantification by gas chromatography–mass spectrometry (Sun and Li, ). The non‐emitters were placed in 1.5 ml microcentrifuge tubes, and both emitters and non‐emitters were weighed on an electronic analytical balance (A200S, 0.0001 g, Sartorius) for calculating the concentration of EβF per milligram of aphid.…”
Section: Methodsmentioning
confidence: 99%
“…These facts prompted us to speculate that there are other sources than aphids themselves responsible for EβF biosynthesis, especially the host plant and endosymbionts of aphids. However, we have recently eliminated the possibility of the host plant and endosymbionts as the sources of the EβF released by aphids by rearing aphids on nonplant artificial diets and by antibiotic treatment respectively (Sun and Li, ). It is therefore most likely that the aphid itself is responsible for EβF biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many FPPS genes have been identified in other insects, including aphid species (Cusson et al ., 2006; Sen et al ., 2007; Lewis et al ., 2008; Taban et al ., 2009; Bomtorin et al ., 2014; Huang et al ., 2015). In our laboratory, we have worked on aphid FPPS genes for many years, including MpFPPS1 and MpFPPS2 in M. persicae (Zhang & Li, 2008, 2012), AgFPPS in the cotton aphid Aphis gossypii (Ma et al ., 2010; Zhang & Li, 2013, 2014; Sun & Li, 2017) and RpFPPS1 and RpFPPS2 in the bird cherry-oat aphid Rhopalosiphum padi (Sun & Li, 2012). In vitro analysis of enzymatic activity with recombinant proteins showed that aphid FPPSs displayed dual geranyl/FPPS activity, and a linked enzymatic assay using the aphid FPPS and peppermint sesquiterpene synthase produced EβF (Lewis et al ., 2008), indicating the potential involvement of aphid FPPS in the biosynthesis of alarm pheromone.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial diet was prepared as previously described (Z. J. Sun & Li, ). Briefly, a two‐way glass tube (⌀3.0 cm) was used, with a 150‐µl diet sealed between two layers of aseptic parafilm at one end and with filter paper covering the other end to prevent aphids from escaping.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it is unclear if EβF released from the aphid is synthesized de novo; until recently, the possibility of the host plant and endosymbionts as the sources of EβF has been eliminated (Z. J. Sun & Li, ). Thus, it is postulated that EβF is synthesized by the aphid, but the molecular mechanism is largely unknown.…”
Section: Introductionmentioning
confidence: 99%